MEDICOLEGAL STUDY ON THE DIAGNOSIS OF DISSEMINATED INTRAVASCULAR COAGULATION (DIC) IN A DEAD BODY (Journal of Forensic Medicine & Toxicology, 2017)
We studied in order to diagnose DIC in a dead body. In a dead body died from DIC and non-DIC we observed and compared the change state of soluble fibrin monomer complex in blood in a cardiac cavity and the detection state of fibrin microthrombi in several organs, and then established DIC diagnostic method.
Keywords: DIC; SFMC; fibrin microthrombi